Targets and Effective Constituents of ZhiziBaipi Decoction for Treating Damp-Heat Jaundice Syndrome Based on Chinmedomics Coupled with UPLC-MS/MS - Wei, Wen-feng; Sun, Hui; Liu, Shao-bo; Lu, Sheng-wen; Zhang, Ai-hua; Wang, Wan-ying; Chai, Wen-jun; Wu, Fang-fang; Yan, Guang-li; Guan, Yu; Wang, Xi-jun (Frontiers in Pharmacology, 2022)
Background: Damp-heat jaundice syndrome (DHJS) is a diagnostic model of traditional Chinese medicine (TCM) that refers to jaundice caused by damp-heat pathogen invasion. DHJS is the most common clinical manifestation of TCM, with yellow skin, yellow eyes and anorexia. ZhiziBaipi Decoction (ZBD) is a classic TCM formula that is effective at treating DHJS and various liver diseases. However, the effective components of ZBD in the context of DHJS and the underlying mechanism are unclear. Purpose: This study of ZBD using the DHJS rat model aimed to elucidate the pathobiology of DHJS and the metabolic targets of therapeutic ZBD, construct the network relationship between the components of ZBD and endogenous biomarkers, and clarify the underlying mechanism of ZBD in preventing and treating DHJS. Methods: Using chinmedomics as the core strategy, an animal model was generated, and the therapeutic effect of ZBD was evaluated based on behavioral, histopathological and biochemical indicators. Metabonomics tools were used to identify biomarkers of DHJS, TCM-based serum pharmacochemistry was used to analyze the effective constituents of ZBD, and chinmedomics technology was used to identify ZBD components highly related to DHJS biomarkers. Results: A total of 42 biomarkers were preliminarily identified, and ZBD significantly affected the levels of 29 of these biomarkers. A total of 59 compounds in ZBD were characterized in vivo. According to chinmedomics analysis, the highly correlated components found in blood were isoformononetin, 3-O-feruloylquinic acid, glycyrrhizic acid, oxyberberine, obaculactone and 5 metabolites. Conclusions: Chinmedomics combined with UPLC-MS/MS was used to study the targets and effective constituents of ZBD for the treatment of DHJS.